SAT0319 SUBCLINICAL ATHEROSCLEROSIS IN INDIAN PATIENTS WITH SCLERODERMA – CLINICAL AND SEROLOGICAL ASSOCIATIONS. (2nd June 2020) - Gangadharan Nair, H.; Rai, M. K.; Singh, M.; Anuja, A.; Singh, K.; Mohindra, N.; Jain, N.; Kumar, S.; Agarwal, V.; Misra, D.
Abstract : Background: Scleroderma has been associated with increased risk of cardiovascular events, however, studies on this from India are sparse.We evaluated clinical and serological factors associated with subclinical atherosclerosis in Indian patients with scleroderma, in a cross-sectional design. Objectives: To compare carotid intima-medial thickness (CIMT, mean value of both carotids) as a measure of subclinical atherosclerosis (SCA) between patients with scleroderma (n=61) fulfilling 2013 ACR/EULAR criteria, and healthy controls (n=41). - To compare clinical (body mass index – BMI, waist-hip ratio – WHR, fasting lipid profile) and serological factors (microparticles, endothelial microparticles, inflammatory cytokines associated with increased cardiovascular risk) between patients with scleroderma and healthy controls. - To identify factors associated with SCA in scleroderma patients. Methods: Subclinical atherosclerosis(SCA) was defined by presence of carotid plaques, or increased CIMT >2 standard deviations compared with Indian reference standards for age and sex. Total microparticles (TMP) were measured of plasma after ultracentrifugation as per previously described protocol using microbeads of 3 μm size (TMP were of size 0.1-1 μm); of these, microparticles positive for CD31 and CD142 were endothelial microparticles (EMP). Serum cytokines (IL-1, IL-6, TNF-α, IL-17) were measured by ELISA using manufacturer instructions. Linear regression was used to identify the determinants of CIMT in scleroderma. Binomial logistic regression was used to identify factors associated with subclinical athersclerosis in scleroderma. Results: Despite lower BMI, triglycerides and VLDL cholesterol, CIMT was significantly higher in patients with scleroderma. Patients with scleroderma had significantly higher total microparticles and endothelial microparticles in plasma, and serum IL-1± and IL-6 (Table 1 ). On multivariable regression, age was the only significant determinant of CIMT. 28 (45.9%) patients had SCA; 13 (21.3%) had carotid plaques. Patients with SCA had higher proportion of males (9/28 in those with SCA vs 2/33 in those without SCA). Binomial logistic regression did not identify any other significant predictors of SCA. Conclusion: Patients with scleroderma had significant burden of subclinical atherosclerosis, which could not be explained by traditional or novel cardiovascular risk factors. References: [1] Psarras A, Soulaidopoulos S, Garyfallos A, Kitas G, Dimitroulas T. A critical view on cardiovascular risk in systemic sclerosis. Rheumatol Int. 2017 Jan; 37(1):85-95. [2] Jung C, Drummer K, Oelzner P, Figulla HR, Boettcher J, Franz M, et al. The association between endothelial microparticles and inflammation in patients with systemic sclerosis and Raynaud's phenomenon as detected by functional imaging. Clin HemorheolMicrocirc. 2015; 61(3):549-557. Acknowledgments: Supported by IRA(Indian Rheumatology Association) Research Grant to DP Misra. Disclosure of Interests: None declared